Restricted plant species on sub-Antarctic Macquarie and Heard Islands - Bergstrom, DM; Turner, PAM; Scott, JJ; Copson, G; Shaw, J (Polar Biology, 2005)
The recent distributional history of two Macquarie Island vascular plant species, Carex trifida, Poa litorosa, and the Heard Island vascular plant, Ranunculus crassipes is examined. C. trifida is known from only one small population on the north west coast of Macquarie Island. Four populations of P. litorosa were first recorded in the 1980s; we believe however, that it was first observed, but misidentified in the 1950s. R. crassipes was first discovered on Heard Island in the late 1980s. We argue that all three species are indigenous and arrived on their respective islands within the last 200 years by natural processes, most likely from warmer neighbouring islands, where these species have more extensive distributions. There have been small-scale changes in distribution of all species, mainly expansion. Further expansion of all three species is expected as a response to warming climate. Feral rabbit grazing is having a confounding negative influence on populations of P. litorosa. Springer-Verlag 2005.